Pemerintahan Militer pada Masa Penjajahan Jepang di Palembang (1942-1945): Tinjauan Historis - M. Razi Pardana; Risa Junita Sari (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This research examines the historical dynamics of the Japanese Empire’s military occupation in Palembang from 1942 to 1945. The primary background of the Japanese invasion of Palembang was the strategic military interest in controlling petroleum resources, specifically the Plaju and Sungai Gerong Refineries, to fulfill the logistical demands of the Greater East Asia War. This study employs a literature review method with a historical approach to reconstruct past events systematically and objectively. The results highlight four key findings: (1) the transition of power occurred rapidly through Blitzkrieg tactics, paralyzing the Dutch East Indies defense; (2) the restructuring of the colonial bureaucracy into a fully military-oriented administration (Palembang Syu); (3) the implementation of a highly exploitative war economy through forced labor and the depletion of natural resources, which triggered immense suffering for the local people; and (4) the formation of the Giyugun volunteer army as Japan’s defensive strategy towards the end of its occupation. It can be concluded that although the Japanese occupation in Palembang was characterized by exploitative suffering, the militarization program through Giyugun inadvertently provided essential military skills that later became a crucial asset for the local youth in defending independence during the Physical Revolution (1945–1949).